Determination of the main components of essential oil extracted from Rosa damascena Mill. and studying the antibacterial activity of it - عزيز, راما (Latakia University Journal -Biological Sciences Series, 2022)
Thiis sttudy was carriied outt tto dettermiin tthe maiin acttiive consttiittuentts of tthe essenttiiall oiill exttractted from Rosa damascena Mill. grown wildly in Syria by using GC-MS technique, and to evalluatte anttiibactteriiall acttiiviitty of tthe oiill agaiinstt ffiive bactteriiall sttraiins.. The results showed that the major compounds were B-Citronellol (47,90%), Trans-Geraneol (8,19%), Linalool (1,90%) respectively, and the oil had great potential of antibacterial activity against some strains.